Exploring the Impact of an Anti-Homophobia and Anti-Transphobia Program on a Teacher Education Program: LGBTQ Pre-Service Teachers Identify Benefits and Challenges - Mitton, Jennifer; Tompkins, Joanne; Kearns, Laura-Lee (Alberta Journal of Educational Research, 2021)
Anti-oppressive pedagogical practices that counter the marginalization of lesbian, gay, bisexual, transgender, two-spirit, queer, and/or questioning youth continue to foster new understanding in teacher education. Researchers note that many pre-service teachers are not prepared to address classroom concerns regarding homophobia, heterosexism, and cisnormativity, fail to identify biases in curricular materials, and resist ideas related to the intersectionality of race, class, ethnicity, gender, ability, and sexuality. While Canadian teacher education programs generally espouse a commitment to equity education, there continues to be a need to provide explicit education on how to create safe and inclusive classrooms and schools for LGBTQ+ learners. The voices of LGBTQ+ pre-service teacher educators are particularly important in terms of understanding what challenges are reduced or remain in teacher education programs adopting an anti-homophobic and anti-transphobic stance. Results from our ongoing work suggests that when faculties of education advocate for safe and positive climates, LGBTQ+ pre-service teachers can bring their full selves into the program. In this article, we explore how the anti-oppressive training related to LGBTQ+ learners and inclusive curricula impacted the experiences of pre-service LGBTQ+ teachers in our program, as presented through their perceptions of who they were in the program, their concerns about who they might be in schools, and their suggestions for acknowledging and implementing anti-oppressive education in formal and informal educational spaces. Key words: Pre-service teacher education; LGBTQ+ teacher candidates; LGBTQ+-inclusive curriculum; anti-oppressive pedagogy; gender identity, and sexual orientation. Les pratiques anti-oppressives pédagogiques qui combattent la marginalisation de jeunes personnes lesbiennes, gaies, bisexuelles, transgenres, bispirituelles, allosexuelles ou en questionnement (LGBTQ+) continuent à favoriser une nouvelle conception de la formation des enseignants. Les chercheurs notent que plusieurs enseignants en formation ne sont pas prêts à traiter des questions en classe qui portent sur l’homophobie, l’hétérosexisme et la cisnormativité; ne savent pas reconnaitre les préjugés dans le matériel pédagogique; et résistent aux idées liées à l’intersectionalité de la race, la classe, l’ethnicité, le genre, la capacité et la sexualité. Alors que les programmes de formation des enseignants au Canada adhèrent de manière générale à un engagement envers l’éducation équitable, le besoin de fournir une éducation explicite sur la création de classes et d’écoles sécuritaires pour les apprenants LGBTQ+ persiste. Les voix des formateurs LGBTQ+ d’enseignants sont particulièrement importantes pour comprendre les défis qui sont amoindris et les défis qui subsistent dans les programmes de formation d’enseignants qui adoptent une position anti-homophobe et anti-transphobe. Les résultats de notre travail en cours portent à croire que lorsque les facultés d’éducation préconisent un climat sécuritaire et positif, les enseignants LGBTQ+ en formation ont l’occasion d’être authentiques et entiers dans le programme. Dans cet article, nous explorons l’impact qu’a eu la formation anti-oppressive en lien avec les apprenants LGBTQ+ et un curriculum inclusif sur les expériences des enseignants en formation dans notre programme, tel que révélé par leurs perceptions de la personne qu’ils étaient dans le programme, leurs préoccupations quant à la personne qu’ils pourraient être dans les écoles et leurs suggestions portant sur la reconnaissance et la mise en œuvre d’une éducation anti-oppressive dans des milieux éducatifs formels et informels. Mots clés : formation des enseignants; enseignants LGBTQ+ en formation; curriculum inclusif des personnes LGBTQ+; pédagogie anti-oppressive; identité de genre; orientation sexuelle